Theory of Stiffness Synthesis by Adding Redundant-actuated Limb on Spatial 6-DOF Parallel Mechanism - Shuangshuang Zhang; Hongtao Yang; Qigeng Liu (Jixie chuandong)
The end stiffness characteristic of the mechanism has great influence on its positioning accuracy， compliance character and dynamic properties. In order to eliminate the configuration singularity， as well as to enhance its stiffness and accuracy， better dynamic property， a controllable stiffness of the mechanism is often required to satisfy different situations. On basis of full degree of freedom parallel mechanism， the design method by adding redundant actuated limbs to realize the end stiffness requirement is analyzed. According to screw theory， the inverse Jacobian matrix of parallel mechanism with limb single drive is analyzed， the mapping relationship matrix from the actuation to the end-effector stiffness is established. Then， the superposition rule of stiffness of each limb to the end stiffness component of the mechanism is analyzed. According to the end stiffness requirement， a stiffness synthesis method by adding redundant-actuated limbs to realize the end stiffness requirement is established. Finally， the Stewart parallel platform is adopted to verify this synthesis method， the design requirement of the end stiffness matrix decoupling is realized.